PELAKSANAAN PENGAWASAN DAN MONITORING PEMBIAYAAN GUNA MEMINIMALISIR RISIKO DALAM PEMBIAYAAN MURABAHAH PADA PT. BNI SYARIAH TBK. CABANG MALANG - AHMAD DWI NURYAWAN; Lutfi Harris (Jurnal Ilmiah Mahasiswa FEB, 2015)
The purpose of this study was to determine the system of supervision and monitoring  on  the  BNI  Syariah  Malang  to  anticipate  the  risk  of  murabahah financing  repayment  problems.  This  study  uses  a  case  study  approach  is  one strategy in a qualitative study. The data were collected by using interviews, interviews, and documentation then analyzed with descriptive methods. To keep the financing provided to customers can be run in accordance with the agreement, the banks need to conduct surveillance and monitoring of such financing. Surveillance and monitoring carried out in order to avoid the possibility of undesirable both for the continuity of financing and the possible risks arising from the provision of such financing. The results of this research is the implementation of the supervision and monitoring of the financing is done BNI Syariah Malang against murabahah financing through two ways, namely by direct supervision and administrative oversight. Comparison of the amount of murabahah financing is channeled to financing problems in BNI Syariah Malang at the level of   Non Performing Financing is still below 5% are included in the category of healthy financing. BNI Syariah Malang should still anticipate and improve the supervision and monitoring of murabahah financing which has been distributed to minimize the financing problems that exist.   Keywords: Control, Monitoring, Murabahah Troubled